Physical and Chemical Surface Modifiers of Carbon Nanotubes on the Mechanical and Physical Properties of Concrete (Journal of Civil Engineering Researchers, 2025)
This study utilizes nanofilament-based nanotechnology, such as carbon nanotubes (CNTs), to improve the mechanical characteristics of concrete as a building material. One of the important and effective factors in adding carbon nanotubes to cement composites is their proper dispersion in the mixture. Therefore, in this research, different methods of dispersing carbon nanotubes in cement mortar have been investigated. They were first functionalized through covalent bonding to prevent carbon nanotubes from accumulating in the water. To achieve the appropriate distribution of carbon nanotubes in water and maintain the stability of their dispersion, different surfactants including Polycarboxylate (PCE), Sodium dodecyl sulfate (SDS), Cetyltrimethylammonium bromide (CTAB), Polyethylene glycol (PEG) were employed. At that point, utilizing visual perception and UV test, PCE/PEG surfactant was presented as a reasonable surfactant for the scattering of carbon nanotubes. Once the most suitable dispersal technique was identified, the impact of incorporating multi-walled carbon nanotubes into concrete was investigated with varying weight proportions. The study revealed that even at low concentrations (0.015%, 0.030%, and 0.045%) relative to the cement weight, the inclusion of carbon nanotubes decreased the porosity of the concrete nanocomposite, resulting in a denser and more compact composite. As a result, it increases the concrete samples' compressive, tensile, and bending strength.
Keywords: Dispersion method; Carbon nanotubes; mechanical properties; Surfactant; Concrete